(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The objective of this work is the survey and analysis of the information and communication technologies adopted in a food company dedicated to the production of baked goods in the city of Mar del Plata, Argentina. To understand how the company generates, transforms, stores and reports data, the interactions of the different information flows in the organization’s internal processes are analyzed by developing process maps, information flow diagrams and technological audits. Based on the initial technological diagnosis, the Soft Operational Research methodology is applied with the purpose of participatively detecting the main weaknesses of the current information system and the impacts they generate in the different areas. As a result, the needs for incorporating information and communication technologies are determined so that the company can face a digital transformation process that allows it to improve the availability of information for decision making and add value to its operations.